Envenomation caused by Latrodectus geometricus in São Paulo state, Brazil: a case report - Almeida, Ricardo Augusto Monteiro de Barros [UNESP]; Ferreira Júnior, Rui Seabra [UNESP]; Chaves, C. R.; Barraviera, Benedito [UNESP] (Universidade Estadual Paulista (Unesp), Centro de Estudos de Venenos e Animais Peçonhentos (CEVAP), 2009)
Widow spiders (Latrodectus spp.), also known as "black widows", have a worldwide distribution and can cause latrodectism. To the best of our knowledge, in Brazil, only one case of Latrodectus geometricus (Koch, 1841) envenomation in a human has been reported. The aim of the present report is to describe a spider bite caused by Latrodectus geometricus in a patient who lives in Paranapanema, São Paulo state, Brazil.
Keywords: Latrodectus geometricus; envenomation; latrodectism; brown widow